THE RIGHT TO HOT PURSUIT IN UNCLOS AND HOT PURSUIT ARRANGEMENTS IN INDONESIA - Yulio Iqbal Cahyo Arsetyo; Supriyono Supriyono (Citra Justicia : Majalah Hukum dan Dinamika Masyarakat, 2023)
After UNCLOS 1982 was in force, Indonesia's position as Archipelago Nation is secure, but there is “compensation” that should be paid by Indonesia to the International community and it was Indonesia should provide Archipelagic Sea Lanes for international ships and Indonesia had to an allowed international ship crossing the Indonesia territorial water by “Peace Passage” concept in UNCLOS 1982, but there is a question about how if an unlawful ship crossing Indonesia Territorial water? Under UNCLOS 1982 the state can do Hot Pursuit to protect its territory but how does Indonesia apply that? The Problem Question regarding this paper will focus on Hot Pursuit Regulations in UNCLOS and Indonesian National Law and how are they applied? The methodology of this research uses literature review with the object of international treaty and uses data and information from internet network tracing which is then expert opinion. The result of the research shows that UNCLOS 1982 had specific rules regarding Hot Pursuit, especially in Article 111, which Hot Pursuit already become a Topic in UNCLOS I before, For Indonesia, the rule of Hot Pursuit already exist in Some of Indonesia's legislature and bill even Indonesia already had special Standart operational procedure regarding conducting Hot Pursuit in Indonesia territory. The right of the state to carry out Hot Pursuit or instant pursuit has existed since the era of the first UNCLOS discussion in Geneva and then resumed at UNCLOS 1982. Indonesia itself as one of the ratifying countries of UNCLOS 1982 has implemented the right of instant pursuit or hot pursuit in state regulations.